PROBLEM-BASED METHODS IN THE EDUCATIONAL PROCESS - Sultonov Ravshanbek Rustamovich; Isomaddinova Umida Mamurjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. In this article, the model of problem-based education in the educational process is designed for students’ thinking, creating a problem situation in children’s minds by posing problems in education; looking for ways to solve the problem, making assumptions; application of the chosen method to the execution of a hypothetical problem; drawing a conclusion on the completed problem, strengthening knowledge by applying the drawn conclusion to practice.